Re-refining of base oil from spent lubricant : a comparative study between laboratory and pilot scale study - Abdul Karim, Azila (2004)
A study on the performance of a pilot scale operation of re-refining used lubricant oil via solvent-extraction process route was conducted to investigate its performance in comparison to the laboratory scale operation. Two dependent variables, namely the Percentage of Sludge Removal (PSR) and Percentage of Oil Loss (POL), were determined and analyzed as the key parameters in measuring the performance of the extraction process, for laboratory as well as pilot scale operations. The performance of the solvent-extraction process in pilot scale was analyzed by varying the solvent-to-oil ratio (SOR) and the amount of potassium hydroxide (KOH) addition, and the results were compared with the data collected from the laboratory scale operation. In addition, the physical properties of spent lubricant and recovered base oil were analyzed and compared between the two scales of operation. In view of the practicality and commercial aspect of the project, the used solvent from previous extraction process was recycled for consecutive run. Thus, the composition of the recovered solvent must be identified to understand its effect on the performance of the solvent-extraction process. Results from the study showed that, in general, the PSR and POL for laboratory and pilot scales operation revealed similar trend of curves, but with expectedly lower performance from the pilot scale study. The main reason of the lower performance from pilot scale operation was due to the change of composite solvents' composition during the solvent-recovery process, which dragged the solvent/oil mixture into the two phase region of the ternary phase diagram. This results in the dispersion of sludge during extraction process. Another factor, which contributed to the difference in the performance of the laboratory and pilot scale study, was the consolidation process. The process simulation, which was carried out for the pilot scale study showed suitability to represent the pilot scale operation, where the data generated from the simulation was acceptable, with percentage error of +lo%.